2019
DOI: 10.3390/jcm8081198
|View full text |Cite
|
Sign up to set email alerts
|

Intraosseous Temperature Change during Installation of Dental Implants with Two Different Surfaces and Different Drilling Protocols: An In Vivo Study in Sheep

Abstract: Background: The intraosseous temperature during implant installation has never been evaluated in an in vivo controlled setup. The aims were to investigate the influence of a drilling protocol and implant surface on the intraosseous temperature during implant installation, to evaluate the influence of temperature increase on osseointegration and to calculate the heat distribution in cortical bone. Methods: Forty Brånemark implants were installed into the metatarsal bone of Finnish Dorset crossbred sheep accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…Many studies have histologically demonstrated that implant insertion could cause overheating or excessive compression of the cortical bone with the formation of microfractures in early MBL [34,35]. Microfractures and overheating of the cortical bone are complications that can occur when placing an implant in an underprepared osteotomy [18,36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have histologically demonstrated that implant insertion could cause overheating or excessive compression of the cortical bone with the formation of microfractures in early MBL [34,35]. Microfractures and overheating of the cortical bone are complications that can occur when placing an implant in an underprepared osteotomy [18,36].…”
Section: Discussionmentioning
confidence: 99%
“…An in vivo study in sheep by Stocchero et al [34] further showed that cortical overheating during implant insertion was a determining factor for bone healing. The study results demonstrated that a higher temperature (approximately 8°C compared to 4°C of the conventionally prepared site) is present in an underprepared site during implant placement, resulting in a smaller amount of peri-implant bone after healing.…”
Section: Lekholm and Zarbmentioning
confidence: 99%
“…Under drilling complications are derived from high insertion torque which may cause bone microfractures and increased temperature generation 27,28 , resulting in compression necrosis of the bone, delayed healing process and increased bone resorption 15,27 . Microfractures occurrence depends on bone density and the discrepancy between the diameter of the implant and the implant's bed 29 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to osteotomy preparation, implant placement itself might also result in a significant temperature increase in an implant osteotomy. Stocchero et al have studied this effect in vivo and found that temperature increase was mainly correlated to the degree of osteotomy under-preparation and associated high-insertion torques (Stocchero et al, 2019). Interestingly, the authors have also shown that osteotomy under-preparation was correlated to higher BIC values but lower bone volumes around the implant.…”
Section: Discussionmentioning
confidence: 99%